Neoarchean Mantle-derived Magmatism within the Repulse Bay Block, Melville Peninsula, Nunavut: Implications for Archean Crustal Extraction and Cratonization - LaFlamme, Crystal; McFarlane, Christopher; Corrigan, David (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2015)
The Repulse Bay block (RBb) of the southern Melville Peninsula, Nunavut, lies within the Rae craton and exposes a large (50,000 km2) area of middle to lower crust. The block is composed of ca. 2.86 Ga and 2.73–2.71 Ga tonalite-trondhjemite-granodiorite (TTG) and granitic gneiss that was derived from an older 3.25 and 3.10 Ga crustal substrate. This period of crustal generation was followed by the emplacement of ca. 2.69–2.66 Ga enderbite, charnockite, and granitoid intrusions with entrained websterite xenoliths. These voluminous batholith-scale bodies (dehydrated and hydrated intrusions), and the associated websterite xenoliths, have similar whole rock geochemical properties, including fractionated light rare earth element (LREE)–heavy (H)REE whole rock patterns and negative Nb, Ti, and Ta anomalies. Dehydrated intrusions and websterite xenoliths also contain similar mineralogy (two pyroxene, biotite, interstitial amphibole) and similar pyroxene trace element compositions. Based on geochemical and mineralogical properties, the two lithologies are interpreted to be related by fractional crystallization, and to be the product of a magmatic cumulate processes. Reworking of the crust in a ca. 2.72 Ga subduction zone setting was followed by ca. 2.69 Ga upwelling of the asthenospheric mantle and the intrusion of massif-type granitoid plutons. Based on a dramatic increase in FeO, Zr, Hf, and LREE content of the most evolved granitoid components from the 2.69–2.66 Ga cumulate intrusion, we propose that those granitoid plutons were in part derived from a metasomatized mantle source enriched by fluids from the subducting oceanic slab that underwent further hybridization (via assimilation) with the crust. Large-scale, mantle-derived Neoarchean sanukitoid-type magmatism played a role in the development of a depleted lower crust and residual sub-continental lithospheric mantle, a crucial element in the preservation of the RBb.